2023
DOI: 10.3390/ijerph20075250
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Distance between the Lines Encircling Pulmonary Veins in Atrial Fibrillation Ablation on First-Pass Isolation Ratio and Clinical Outcomes

Abstract: Introduction: How wide the encircling line is made may influence the outcomes of pulmonary vein isolation (PVI). In the present study we hypothesised that the distance between the lines encircling the pulmonary veins may correspond with the extent of wide antral circumferential ablation (WACA). The aim of the study was to assess the impact of the distance and the area between the lines on the posterior wall of the left atrium on first-pass isolation rate and 12-month freedom from atrial arrhythmia in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In contrast to PVI modifications or adjuncts with no proven efficiency, the accuracy of our suggestion is reflected by results of the AUC analysis showing significant strength of prediction. Interestingly, in a study by Krzyżanowski et al, 18 DBL showed no impact on AF recurrence in the long -term follow -up of first -pass isolation. The contradiction between our findings may arise from methodologic differences.…”
Section: Follow -Up Of the Patientsmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast to PVI modifications or adjuncts with no proven efficiency, the accuracy of our suggestion is reflected by results of the AUC analysis showing significant strength of prediction. Interestingly, in a study by Krzyżanowski et al, 18 DBL showed no impact on AF recurrence in the long -term follow -up of first -pass isolation. The contradiction between our findings may arise from methodologic differences.…”
Section: Follow -Up Of the Patientsmentioning
confidence: 93%
“…Firstly, in the mentioned study, DBL was measured between the uppermost and the lowest points of 2 opposite isolation lines, while in our study it was measured between the nearest points (FIGuRE 5). Moreover, and perhaps more importantly, Krzyżanowski et al 18 did not index the DBL to the total LA diameter. Therefore, in the case of enlarged atria, even with high DBL values, isolation lines might be far from the PVs.…”
Section: Follow -Up Of the Patientsmentioning
confidence: 99%